B-Lines by Lung Ultrasound Can Predict Worsening Heart Failure in Acute Myocardial Infarction During Hospitalization and Short-Term Follow-Up - He, Jiexin; Yi, Shixin; Zhou, Yingling; Hu, Xiangming; Lun, Ziheng; Dong, Haojian; Zhang, Ying (Frontiers in Cardiovascular Medicine, 2022)
Background: Acute myocardial infarction (AMI) with pulmonary edema shows a worse prognosis. Lung ultrasound (LUS) is a new tool for evaluating subclinical pulmonary congestion. It has been proved to predict prognosis in heart failure; however, whether it can be used as a short-term prognostic marker in AMI and provide incremental value to Killip classification is unknown. Methods: We performed echocardiography and LUS by the 8-zone method in patients enrolled in Guangdong Provincial People’s Hospital undergoing percutaneous coronary intervention for AMI from March to July 2021. The lung water detected by LUS was defined as B-lines, and the sum of the B-line number from 8 chest zones was calculated. Besides, the classification into LUS according to the pulmonary edema severity was as follows: normal (B-line numbers <5), mild (B-line numbers ≥5 and <15), moderate (B-line numbers ≥15 and <30), and severe (B-line numbers ≥30). The NT-proBNP analysis was performed on the same day. All patients were followed up for 30 days after discharge. The adverse events were defined as all-cause death, worsening heart failure in hospitalization, or re-hospitalization for heart failure during the follow-up. Results: 63 patients were enrolled consecutively and followed up for 30 days. The number of B-lines at admission (median 7[3–15]) was correlated with NT-proBNP (r=0.37, p = 0.003) and negatively correlated with ejection fraction (r=-0.43; p ＜0.001) separately. In the multivariate analysis, B-line number was an independent predictor of short-term outcomes in AMI patients (in-hospital, adjusted OR 1.13 [95% CI: 1.04–1.23], P= 0.006; 30-day follow-up, adjusted OR 1.09 [95% CI: 1.01–1.18], P= 0.020). For in-hospital results, the area under the receiver operating characteristic curves (AUCs) were 0.639 (P=0.093), 0.837 (P<0.001), and 0.847 (P<0.001) for Killip, LUS and their combination, respectively. For the diagnosis of 30-day adverse events, the AUCs were 0.665 for the Killip classification (P=0.061), 0.728 for LUS (P=0.010), and 0.778 for their combination (P=0.002). Conclusion: B-lines by lung ultrasound can be an independent predictor of worsening heart failure in AMI during hospitalization and short-term follow-up and provides significant incremental prognostic value to Killip classification.